Children's health issues in historical perspective - Strong-Boag, Veronica Jane; Warsh, Cheryl Krasnick, 1957- (Wilfrid Laurier University Press, 2005)
From sentimental stories about polio to the latest cherub in hospital commercials, sick children tug at the public's heartstrings. However sick children have not always had adequate medical care or protection. The essays in this book investigate the identification, prevention, and treatment of childhood diseases from the 1800s onwards, in areas ranging from French-colonial Vietnam to nineteenth-century Northern British Columbia, from New Zealand fresh air camps to American health fairs. Themes include: the role of government and/or the private sector in initiating and underwriting child public health programs; the growth of the profession of paediatrics and its views on 'proper' mothering techniques; the role of nationalism, as well as ethnic and racial dimensions in child-saving movements; normative behaviour, social control, and the treatment of 'deviant' children and adolescents; poverty, wealth, and child health measures; and the development of the modern children's hospital.; This liberally illustrated collection reflects the growing academic interest in all aspects of childhood, especially child health, and originates from health care professionals and scholars across the disciplines. An introduction by the editors places the historical themes in context and offers an overview of the contemporary study of children's health.